2019
DOI: 10.1002/2475-8876.12098
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on mental health‐care effects of plant installations in office spaces

Abstract: Offices may have different indoor environmental quality related problems, such as space, indoor air quality, office workers’ thermal comfort, productivity, and mental stress. The objective of this study was to examine the effect of indoor plants on physiological/psychological responses and productivity, and to examine the mental healthcare status of office workers. To clarify the effect of indoor plants, we conducted a demonstration experiment in two rooms of an office. The experiment was performed in two offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Smith et al (2017) also identified a positive impact of plants on work environment aesthetics in an office in the same building with plants compared with a control office without plants. Moreover, Genjo et al (2019) examined the green mental healthcare effect of plants on office workers. This study stated that plants have a mental recovery effect on the visual and subjective fatigue symptoms of office workers, such as drowsiness, dullness, and inability to concentrate.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (2017) also identified a positive impact of plants on work environment aesthetics in an office in the same building with plants compared with a control office without plants. Moreover, Genjo et al (2019) examined the green mental healthcare effect of plants on office workers. This study stated that plants have a mental recovery effect on the visual and subjective fatigue symptoms of office workers, such as drowsiness, dullness, and inability to concentrate.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the participants, however, were college students. Only six studies recruited office workers [ 54 , 55 , 56 , 57 , 58 , 59 ], five studies recruited patients [ 60 , 61 , 62 , 63 , 64 ], two studies recruited junior high school students [ 65 , 66 ], and one study recruited high school students as participants [ 67 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 42 records, 20 reported the specific number of indoor potted plants as the intervention; the highest number of potted plants was 34 [ 66 ], and the lowest number of potted plants was one [ 56 , 59 , 60 , 68 , 69 , 70 , 71 ]. Three papers reported the green coverage ratio, with the highest at 10% and the lowest at 3% [ 57 ]. Two papers also indicated the volume of indoor plants as a percentage of the total experimental space, where the largest volume was 17.9% [ 53 ] and the smallest was 5% [ 67 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spaces providing mental refreshment are described by R. and S. Kaplan with four primary characteristics: 1. a location that is both physically and mentally distant from the workstation; 2. a design different from the work environment, which helps to divert thoughts from the activity performed so far by new stimuli; 3. proximity to nature or some refreshing environment [38]; 4. a design in line with the function of the space, compatibility.…”
Section: Conceptmentioning
confidence: 99%